Functional Reconstruction of Temporomandibular Joint after Resection of Pigmented Villonodular Synovitis with Extension to Infratemporal Fossa and Skull Base: A Case Report - Vellutini, Eduardo de Arnaldo Silva; Alonso, Nivaldo; Arap, Sérgio Samir; Godoy, Luís Felipe Silva; Souza e Souza, Ricardo Antenor de; Mattedi, Rômulo Loss; de Oliveira, Matheus Fernandes (The Surgery Journal, 2016)
Introduction Pigmented villonodular synovitis (PVNS) is a benign but aggressive lesion arising from sinovia. The temporomandibular joint (TMJ) is hardly ever involved.Methods We describe a case of PVNS arising in the left TMJ involving infratemporal fossa soft tissue and the skull base; we also present the reconstruction.Results A 37-year-old woman had progressive mandibular swelling for 6 months. Computed tomography of the skull revealed an osteolytic lesion in the left TMJ, involving the upper mandible, condyle, and glenoid fossa and extending to the infratemporal fossa and fossa media through a defect in temporal bone. Surgical management included a left pterional craniotomy to reach the temporal skull base and resect the intracranial tumor and a facial approach with partial left mandibulectomy and resection of left condyle, glenoid fossa, and tumor removal in infratemporal fossa. Mandible function was restored with prosthetic reconstruction of the condyle. She progressively started to eat solid foods after 3 months, becoming increasingly functional and asymptomatic. At 30 months' follow-up, she had no sign of tumoral recurrence and showed asymptomatic and normal TMJ function.Conclusion PVNS should be considered in the differential diagnosis of bone neoplasms affecting young patients. In such cases, radical excision is mandatory and TMJ prosthesis for local reconstruction may be used to preserve functionality.
Keywords: temporomandibular joint; skull base; synovitis; treatment